ON CERTAIN FACTORS OF SPOUSES’ PERCEPTION OF EACH OTHER AND MARITAL SATISFACTION - Fazilov Botir Bokhadirovich (Sciental Journals Publishing, 2025)
This thesis presents an analysis of key theoretical approaches to the study of marital satisfaction in psychological science. Various aspects of marriage and the relationships between spouses are examined.
Keywords: family, marriage, marital and family relationships, marital satisfaction, divorce, married couple.